Lonely planet slovenia - Fallon, Steve ([S.l.] : Lonely Planet, 2010)
No one knows Slovenia like Lonely Planet. We were the pioneers of a Slovenia guide, after all. We know the best ski spots in the Julian Alps, the most blissed-out spa experiences in Stajerska, the coolest white-water rafting in the Soca Valley and the spookiest caves in Europe. Whatever you're looking for, this 6th edition will tell you all you need to know. Lonely Planet guides are written by experts who get to the heart of every destination they visit. This fully updated edition is packed with accurate, practical and honest advice, designed to give you the information you need to make the most of your trip. In This Guide: Local Tips and regional itineraries get you to the heart of the country Expanded activities coverage shows you how to get the best out of Slovenia's exciting landscapes Color Highlights help you plan your trip.
Keywords: Slovenia; Travel